Erosion and sedimentation problems in Nepal from the viewpoint of morphological development - Higaki, Daisuke (Journal of Nepal Geological Society, 1998)
Three cases of disasters such as landslides, debris flows and unstable river courses are presented from the viewpoint of morphological development in Nepal. In the Tukuche village in the Higher Himalaya, shallow landslides occur in moraine deposits covered with recent fluvial deposits promoting bank erosion of the Kali Gandaki River. The slope towards the river bank composed of Quaternary glacial deposits should be noticed as landslide-prone areas in this region. Alluvial fans are less developed and widths of river courses are larger on the rivers originating from the Upper Siwaliks than those from the Middle/Lower Siwaliks in the eastern Churia hills. Because material size produced from hill slopes is smaller in the former case than the latter case, less tractive force by river stream can transport river bed materials and erode river banks. Consequently, the river topography is altered dramatically. River course control works are very important for the former case. Countermeasures for the torrents affected by debris flows in 1981 are also discussed in this paper. Distribution and volume of unstable deposits depend on the stage of morphological development of a torrent watershed. Analysis of morphological development was carried out on the basis of mapping and volume estimation of unstable deposits on the slopes and valley floors in two torrent watersheds of the Nallu Khola in the Mahabarat Range.